A Novel Concatenated Coding Scheme: RS-SC-LDPC Codes - Qiu, Jie; Chen, Li; Liu, Shiqiu (IEEE communications letters, 2020)
A novel concatenated coding scheme is introduced, where the Reed-Solomon (RS) code is concatenated with the spatially coupled low-density parity-check (SC-LDPC) code, namely the RS-SC-LDPC code. We first propose the locally systematic encoding of the inner code and its termination when considering the concatenated code has a finite length. A decoding scheme is then proposed, in which the belief propagation (BP) based sliding window decoding (SWD) decodes the inner code with the assistance of the outer Berlekamp-Massey (BM) decoding feedback. This research shows the RS-SC-LDPC codes can achieve a high decoding performance without yielding an error floor until the bit error rate (BER) of 10 −8 . They also significantly outperform the incumbent RS-convolutional concatenated (RS-CC) codes, as well as the BCH-SC-LDPC codes.